Một số khó khăn của học sinh khi học trực tuyến trong bối cảnh dịch bệnh Covid-19: nghiên cứu trường hợp tại Trường Trung học phổ thông chuyên Nguyễn Bỉnh Khiêm, tỉnh Vĩnh Long - Ngô , Thanh Trúc (Tạp chí Giáo dục, 2022)
During the serious situation of Covid-19 pandemic over all the world, Vietnam must strictly implement the proposed Covid-19 prevention and control measures. In particular, schools were forced to close to restrain the spread of the disease. Faced with these challenges, Nguyen Binh Khiem High School for the Gifted has shifted to online learning to promptly respond to the complicated developments of the Covid-19 epidemic. This study based on surveys and in-depth interviews from a high school has shown that: encountering Internet connection disruption when learning online, being distracted due to the lack of a private space to study online and often being affected by background noise while learning online are common challenges among online students. It is essential for school leaders as well as authorities at all levels to tackle with support and solutions for learners. Finally, the researcher recommends continuing teacher and student training with knowledge and skills to meet the requirements of digital transformation and strengthening cooperation with parents when they study at home.